KORELASI KEMAMPUAN TES MEMBACA TERHADAP PEMAHAMAN SISWA PADA TEMA BACAAN - Henny Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Reading is a process carried out and used by the reader to get the message to be conveyed by the author through the medium of words / written language. The main purpose of reading is to find and obtain information, in the form of content, understanding the meaning of reading. The reading ability test is intended to measure the level of students' congressive abilities, understanding written discourse in the form of congritive levels of memory (C1), understanding (C2), Application (C3), Analysis (C4), Synthesis (C5), and evaluation (C6). In the choice of discourse, it should consider in terms of the level of difficulty, content, length and form of discourse. The discourse that is tested can be in the form of prose, dialogue, or poetry by considering the lengths.